2015
DOI: 10.21548/36-2-962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Unsaturated Fatty Acids on Fatty Acid Composition of Saccharomyces cerevisiae and Major Volatile Compounds in Wine

Abstract: The synergistic influences of three unsaturated fatty acids (UFAs, namely linoleic acid, oleic acid and linolenic acid) on the fatty acid composition of Saccharomyces cerevisiae and major volatile compounds were investigated in synthetic grape juice. The addition of UFAs led to a corresponding increase in UFAs in the cellular lipid, which was accompanied by a reverse reduction in the content of medium-chain saturated fatty acids (C6:0 to C14:0) and little variation in that of long-chain saturated fatty acids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 43 publications
7
54
1
Order By: Relevance
“…It is well known that the accumulation of precursors, higher alcohols and MCFAs in the medium can promote the production of acetate esters and ethyl esters, respectively (Mouret et al 2014, Duan et al 2015. This could mainly explain the higher concentration of esters produced in wine with addition of BCAAs (Table 5), although few genes related to production of esters were induced.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is well known that the accumulation of precursors, higher alcohols and MCFAs in the medium can promote the production of acetate esters and ethyl esters, respectively (Mouret et al 2014, Duan et al 2015. This could mainly explain the higher concentration of esters produced in wine with addition of BCAAs (Table 5), although few genes related to production of esters were induced.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, it has been confirmed that higher yeast biomass can guarantee greater fermentation activity and promote the production of aroma compounds, including higher alcohols and esters (Varela et al 2004, Duan et al 2015. The increase in yeast biomass could therefore partially contribute to the increase in volatile aroma compounds in fermentations with added BCAAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds can directly contribute to the flavour of wine, or serve as substrates that participate in the formation of ethyl acetates. The C6, C8 and C10 medium-chain fatty acid ethyl esters are important flavour-active metabolites that are responsible for the highly desired fruit aroma character in wine (Duan et al, 2015). Fatty acids have also been described with fruity, cheesey, fatty and rancid notes.…”
Section: Fernandes N C M Et Almentioning
confidence: 99%